FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN PADA TOKO KOSMETIK CANDRA SEMARANG - Adinda Pandjiaz Tantri; Tantri Widiastuti (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2013)
The objective of this research was to find out the infuence of variable of product quality, price, service quality, emotional factor, cost and ease towards simultaneously and partially influenced the customer satisfaction of customer at Toko Kosmetik Candra. The population in this research was all customers of Toko Kosmetik Candra and the samples were 100 customers with the technique sampling was convenience sampling method. The analysis tool used was multiple linear regression. The results of simultaneous analysis (F test) indicated that the variables of product quality (X1), price (X2), service quality (X3), emotional factor (X4), cost and ease towards (X5) had significant influence to customer satisfaction at Toko Kosmetik Candra with significance rate 0,000. Meanwhile, the partial analysis (t-test) showed that the variable of product quality (X1) had significant influence to customer satisfaction, price (X2) had significant influence to customer satisfaction, service quality (X3) had significant influence to customer satisfaction, emotional factor (X4) had significant influence to customer satisfaction, cost and ease towards (X5) had significant influence to customer satisfaction.